THE RESULTS OF SURGICAL TREATMENT OF PATIENTS WITH ADRENAL TUMORS - A. A. Kostin; N. V. Vorobyev; A. O. Tolkachev; A. G. Muradyan; S. V. Popov (Исследования и практика в медицине)
Malignant adrenal tumors such as adrenocortical cancer (ACC) and malignant pheochromocytoma (MPCC) have a particularly aggressive course, leading to higher mortality in these patients, especially in the later stages of the disease. In this regard, there is a statistically significant difference in survival of patients, depending on the time of detection and initiation of treatment.Purpose. Analysis of the results of surgical treatment of patients with adrenal tumors.Patients and methods. 55 patients aged from 17 to 75 years (median 50 ± 13 years) with primary tumor neoplasms of the adrenal gland underwent surgical treatment in the period from 1999 to 2014 in the Department of Onco-urology, P. Hertsen MORI. 18 adrenalectomy (32,7%) completed laparoscopy, 36 (65,5%) – open access, 1 (1,8%) – videoassistance. Among them, retroperitoneal lymph node dissection with ipsilateral hand made in 14 (25.5%), combined operations with resection of adjacent organs – 7 (12,7%), thrombectomy with resection of the inferior Vena cava – 3 (5,5%) cases. The median time was 100 ± 73 minutes in open surgical procedures – 183 ± 55 minutes, laparoscopic – 60 ± 30 minutes. The volume of blood loss – 300 ± 1136 ml. According to the routine morphological studies, 24 (43,6%) patients the tumor were benign, the remaining 31 (56,4%) – malignant.Results. Long-term results have been traced in 84% of patients in group with ACC. The observation time for patients varied from 2 to 167 months, with a median of 64.5 (IQR 22–111) months. Median survival without progression and 5-year overall and tumor survival was: I stage – 93 months and 67 ± 13%, II stage – 30 months and 75 ± 21%, III stage– 18 months and 67 ± 27%, IV stage – 10 months and 25 ± 21%. The observation time for patients with MPCC varies from 12 to 102 months, with a median of 60 (IQR 18–102) months. Median survival without progression was 26 (IQR 15 to 38) months, 5-year overall and tumor survival was 33 ± 27%.Conclusion. Currently, the main objective is the identification and operative treatment of malignant tumors of the adrenal glands in the early stages of the disease, which allows to improve the results of relapse-free and  overall survival. In our opinion, it is appropriate extension of the indications for volumes of surgical treatment for primary generalized forms identified with the presence of solitary metastases, and active surgical tactics in the progression of neoplastic process.